1984
DOI: 10.1007/bf00276629
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of sodium gating currents in the squid giant axon

Abstract: Asymmetric displacement currents, Ig, were measured in squid axons at different hydrostatic pressures, P, up to 60 MPa. Potassium and sodium currents were abolished by intracellular Cs+ and TEA+, by extracellular Tetrodotoxin (TTX), and by Na+ substitution with Tris+. The time course of Ig became progressively slower with increasing pressure, and the amplitude decreased. With appropriate scaling in time and amplitude, Ig records at any given P could be made to superimpose very well with those obtained at atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 36 publications
4
41
0
Order By: Relevance
“…It is surprising that Qon(E) curves are shifted to the left, whereas PNa(E) curves are shifted to the right when temperature is increased. A similar observation has been reported by Conti et al (1982Conti et al ( , 1984, who found that increasing pressure shifts PNa(E) towards positive potentials, but does not shift Qon(E). The results of the present paper and the findings of Conti et al (1982Conti et al ( , 1984 can be explained with the hypothesis that transitions between the closed states of the Na channel contribute far more to the total charge movement than the final step preceding the opening of the Na channel.…”
Section: Comparison With Previous Resultssupporting
confidence: 70%
“…It is surprising that Qon(E) curves are shifted to the left, whereas PNa(E) curves are shifted to the right when temperature is increased. A similar observation has been reported by Conti et al (1982Conti et al ( , 1984, who found that increasing pressure shifts PNa(E) towards positive potentials, but does not shift Qon(E). The results of the present paper and the findings of Conti et al (1982Conti et al ( , 1984 can be explained with the hypothesis that transitions between the closed states of the Na channel contribute far more to the total charge movement than the final step preceding the opening of the Na channel.…”
Section: Comparison With Previous Resultssupporting
confidence: 70%
“…However, the apparent activation volumes describing the pressure dependencies of a* and 13* are expected to be weighted functions of several AVts and depend also on the relative probability of the various channel states. The effects described here, as well as those observed for ionic channels in nerves (5)(6)(7)(8)24) are readily appreciable only above 10 MPa. Therefore, they are unlikely to play a major role in the physiology ofthe high pressure nervous syndrome, which can develop in whole organisms at pressures as low as 6 MPa (3).…”
Section: Discussionsupporting
confidence: 49%
“…The last step, however, could be uncharged and not too fast because the sequence may have slower steps as it gets closer to the open state. Conti et al (1984) have determined the activation volume of the gating reaction by measuring gating currents and ionic currents at high hydrostatic pressures. They found that the activation volume determined from the gating current is less than the volume measured from the sodium current.…”
Section: Uncharged Stepsmentioning
confidence: 99%